Pengaruh Sharia Compliance dan Good Corporate Governance Terhadap Fraud Pada Bank Umum Syariah di Indonesia Periode 2019-2022 - Sriyani Sriyani; Youdhi Prayogo; Laily Ifazah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the influence of Sharia Compliance and Good Corporate Governance on Fraud in Sharia Commercial Banks in Indonesia. The period in this research is 4 years from 2019 to 2022. This research uses secondary data such as financial reports and reports on the implementation of Good Corporate Governance. The sampling technique in this research is Purposive Sampling. This research uses multiple linear regression analysis. The independent variable in this research uses Sharia Compliance with the proxies Islamic Income Ratio, Profit Sharing Ratio, Zakat Performance Ratio and Good Corporate Governance. Meanwhile, the dependent variable uses Fraud at Sharia Commercial Banks in Indonesia. The results of this research show that the Islamic Income Ratio has a significant effect on fraud, the Profit Sharing Ratio has no significant effect on fraud, the Zakat Performance Ratio has no significant effect on fraud, and Good Corporate Governance has a significant effect on fraud. Meanwhile, simultaneously it shows that the variables Islamic Income Ratio, Profit Sharing Ratio, Zakat Performance Ratio and Good Corporate Governance have a significant effect on fraud in Sharia Commercial Banks in Indonesia.